Adult Stem Cell Niches - Wislet-Gendebien, Sabine (IntechOpen, 2014)
Tissue-specific stem cells have the capacity to self-renew and differentiate into several types of functional cells that replenish lost cells throughout an organism?s lifetime. Studies on stem cells from diverse systems have shown that stem cell function is controlled by extracellular cues from the niche and by intrinsic genetic programs within the stem cell. The objectives of this book would be to review the molecular mechanisms that mediate the balanced response of stem cells to the needs of the organisms. Likewise, niches have also been linked to pathologies, by imposing aberrant function on stem cells or other targets. Therefore, the second objective of this book would be to highligh the molecular dysregulation of niche biology leading to the disease. The third objective would be to review the therapeutical targets described within stem cell niches.